Worlds in Miniature : Contemplating Miniaturisation in Global Material Culture - Dixon, Charlotte; Davy, Jack; Project Muse. (London : UCL Press, 2019)
Worlds in Miniature brings together researchers working across different regions, time periods and disciplines to explore the subject of miniaturisation as a material culture technique.
Cover; Half Title; Title Page; Copyright Page; Contents; List of figures; List of tables; Contributors; Acknowledgements; 1. What makes a miniature?; 2. Exmoor's minilithic enigma; 3. Miniaturisation in early Egypt; 4. Miniaturisation among the Makah; 5. Interview with boat model-makers, Cliff Swallow and Pat Howard; 6. Miniaturising boats: the case of the Indian masula surf boat; 7. Composing Warao indigeneity and miniatures; 8. A sense of scale; 9. Interview with Henry Milner, architectural model-maker; 10. Some thoughts on the measure of objects; Index
Description based on print version record.
Keywords: Miniature objects; Miniature craft; Material culture; Miniature craft; Miniature objects; Material culture; Electronic books